2019
DOI: 10.3390/md17020096
|View full text |Cite
|
Sign up to set email alerts
|

Glycerolipid Composition of the Red Macroalga Agarophyton Chilensis and Comparison to the Closely Related Agarophyton Vermiculophyllum Producing Different Types of Eicosanoids

Abstract: The red macroalga Agarophyton chilensis is a well-known producer of eicosanoids such as hydroxyeicosatetraenoic acids, but the alga produces almost no prostaglandins, unlike the closely related A. vermiculophyllum. This indicates that the related two algae would have different enzyme systems or substrate composition. To carry out more in-depth discussions on the metabolic pathway of eicosanoids between the two algae, we investigated the characteristics of glycerolipids, which are the substrates of eicosanoids … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…In contrast, the total content of omega-6 fatty acids was higher (Table 1). ARA is the precursor of eicosanoids and oxylipins, bioactive lipidic promoters of the defense response in seaweed (19, 20). Most natural and endogenous PPARγ ligands are derived from ARA metabolization (84); therefore, the increased abundance in this seaweed extract may account for its high PPARγ transactivation capacity.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In contrast, the total content of omega-6 fatty acids was higher (Table 1). ARA is the precursor of eicosanoids and oxylipins, bioactive lipidic promoters of the defense response in seaweed (19, 20). Most natural and endogenous PPARγ ligands are derived from ARA metabolization (84); therefore, the increased abundance in this seaweed extract may account for its high PPARγ transactivation capacity.…”
Section: Resultsmentioning
confidence: 99%
“…This interest is paralleled with an increase in the study of the biomedical potential of seaweed due to the large amounts of bioactive molecules they possess (11,9092). The study of the lipid components of A. chilense and other closely related red seaweeds had demonstrated the presence of PUFAs and eicosanoids (19,22,37); however, whether the lipids present in the Agarophyton genus were able to activate PPARγ and had insulin sensitizer and antioxidant effects in vivo was unknown. Here, we demonstrated that A.chilense oleoresin includes ligands that are able to activate PPARγ with a similar level of activation to that observed with the partial PPARγ activators FMOC-Leu and INT131.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations